2007
DOI: 10.1007/s10616-007-9060-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving heterologous protein expression in transfected Drosophila S2 cells as assessed by EGFP expression

Abstract: Drosophila melanogaster S2 cells were co-transfected with plasmid vectors containing the enhanced green fluorescent protein gene (EGFP), under the control of metallothionein promoter (pMt), and the hygromycin selection gene, in view of establishing parameters for optimized gene expression. A protocol of transfection was worked out, leading after hygromycin selection, to approximately 90% of S2MtEGFP fluorescent cells at day 5 after copper sulfate (CuSO(4)) induction. As analyzed by confocal microscopy, S2MtEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
(32 reference statements)
2
16
0
11
Order By: Relevance
“…While this latter point was successfully addressed in a dedicated paper describing how recombinant S2 cells could be easily and advantageously cultured using scaleable bioreactors (Brillet et al 2006), we have explored some of the routes that could be envisioned to here optimize the expression yields and functionality of EGFP-fused receptors. Consistent with previous observations for various heterologous proteins (Yokomizo et al 2007;Santos et al 2007;Perret et al 2003), recombinant S2 cells were heterogeneously expressing EGFP-hMOR fusions. Thus, as a first improvement step, cell sorting techniques were assayed for enriching the polyclonal S2 cell lines in receptor-expressing sub-populations.…”
Section: Distribution Of Functional Egfp-hmor Among Subcellular Membrsupporting
confidence: 91%
“…While this latter point was successfully addressed in a dedicated paper describing how recombinant S2 cells could be easily and advantageously cultured using scaleable bioreactors (Brillet et al 2006), we have explored some of the routes that could be envisioned to here optimize the expression yields and functionality of EGFP-fused receptors. Consistent with previous observations for various heterologous proteins (Yokomizo et al 2007;Santos et al 2007;Perret et al 2003), recombinant S2 cells were heterogeneously expressing EGFP-hMOR fusions. Thus, as a first improvement step, cell sorting techniques were assayed for enriching the polyclonal S2 cell lines in receptor-expressing sub-populations.…”
Section: Distribution Of Functional Egfp-hmor Among Subcellular Membrsupporting
confidence: 91%
“…By using the DES, several authors reported a good level of recombinant protein expression as compared to other expression systems (Angelichio et al, 1991;Culp et al, 1991;Deml et al, 1999;Hill et al, 2001;Jorge et al, 2008;Lee et al, 2000;Li et al, 1996;Nilsen and Castellino, 1999;Santos et al, 2007;Yokomizo et al, 2007). In addition, DES has been reported to have advantageous bioprocess characteristics, such as high cell density attained, low cost culture medium needed and continuous bioprocess possibility (Affleck and Walker, 2008;Batista et al, 2008Batista et al, , 2009Bovo et al, 2008;Brillet et al, 2008;Galesi et al, 2008;Iwaki and Castellino, 2008;Jorge et al, 2008;Park et al, 2008;Santos et al, 2007;Swiech et al, 2008aSwiech et al, , 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DES has been reported to have advantageous bioprocess characteristics, such as high cell density attained, low cost culture medium needed and continuous bioprocess possibility (Affleck and Walker, 2008;Batista et al, 2008Batista et al, , 2009Bovo et al, 2008;Brillet et al, 2008;Galesi et al, 2008;Iwaki and Castellino, 2008;Jorge et al, 2008;Park et al, 2008;Santos et al, 2007;Swiech et al, 2008aSwiech et al, , 2008b. In previous publications Yokomizo et al, 2007) we have shown that the DES indeed represents a novel and promising approach for the production of the rabies virus glycoprotein (RVGP).…”
Section: Introductionmentioning
confidence: 99%
“…Specialized media, transfection reagents, and vectors have been developed in response to recent advances in insect cell culture and molecular biology methods. Nevertheless, in BEVS the infection step necessary for protein expression does not allow a continuous bioprocess system; also, proteolysis is a problem due to the BEVS lytic nature and can affect the quality and quantity of product; and finally, recombinant baculovirus may loose infectivity with increasing number of passages (Santos et al 2007;McCarroll and King 1997).…”
Section: Introductionmentioning
confidence: 99%